2016
DOI: 10.1371/journal.ppat.1005527
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus bombysepticus α-Toxin Binding to G Protein-Coupled Receptor Kinase 2 Regulates cAMP/PKA Signaling Pathway to Induce Host Death

Abstract: Bacterial pathogens and their toxins target host receptors, leading to aberrant behavior or host death by changing signaling events through subversion of host intracellular cAMP level. This is an efficient and widespread mechanism of microbial pathogenesis. Previous studies describe toxins that increase cAMP in host cells, resulting in death through G protein-coupled receptor (GPCR) signaling pathways by influencing adenylyl cyclase or G protein activity. G protein-coupled receptor kinase 2 (GRK2) has a centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 62 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…A great deal of work is being done to characterize these hypothetical pathways and GPCR downstream effectors in insects [ 27 , 34 , 118 , 119 , 120 , 121 ]. Studies have revealed specific GPCR genes and their potential biological functions that may impact insects’ physiology [ 21 , 22 ], including their reproduction [ 23 , 24 , 25 , 26 , 27 , 28 ], and regulating their growth and development [ 27 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], as well as their stress responses [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], their feeding patterns [ 27 , 32 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], their other behaviors [ 23 , 61 , 62 ,…”
Section: Gpcrs and The Regulatory Pathways Governing The Biological And Physiological Processes Of Organismsmentioning
confidence: 99%
“…A great deal of work is being done to characterize these hypothetical pathways and GPCR downstream effectors in insects [ 27 , 34 , 118 , 119 , 120 , 121 ]. Studies have revealed specific GPCR genes and their potential biological functions that may impact insects’ physiology [ 21 , 22 ], including their reproduction [ 23 , 24 , 25 , 26 , 27 , 28 ], and regulating their growth and development [ 27 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], as well as their stress responses [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], their feeding patterns [ 27 , 32 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], their other behaviors [ 23 , 61 , 62 ,…”
Section: Gpcrs and The Regulatory Pathways Governing The Biological And Physiological Processes Of Organismsmentioning
confidence: 99%
“…As one of the key environmental stimuli, amino acids can be sensed by G protein coupled receptor (GPCR) (Fujiwara et al, ; Wauson, Zaganjor, & Cobb, ). Previous reports have shown that GPCRs can activate PKC (Cattaneo, Parisi & Ammendola, ) and PKA (Lin et al, ), which two can phosphorylate AnxA2. And some GPCRs can regulate the levels of matrix metalloproteinase 2 (MMP2) and MMP9 of protease (Liu et al, ).…”
Section: Introductionmentioning
confidence: 97%
“…Different letters above the bars indicate significant differences (p < 0.05) according to the SAS software activation of PKA, etc. that induced host death (Lin et al 2016). In our study, we found that the survival rate of bees was high, approximately 70% when they were injected only with dsSp1, compared with the survival rate of dsSp1-treated adults injected with Bb that was significantly decreased to approximately 10-20% ( Fig.…”
Section: Discussionmentioning
confidence: 49%